2018
DOI: 10.1161/jaha.118.011079
|View full text |Cite
|
Sign up to set email alerts
|

Do Out‐of‐Hospital Cardiac Arrest Patients Have Increased Chances of Survival When Transported to a Cardiac Resuscitation Center?

Abstract: Background Patients suffering from an out‐of‐hospital cardiac arrest are often transported to the closest hospital. Although it has been suggested that these patients be transported to cardiac resuscitation centers, few jurisdictions have acted on this recommendation. To better evaluate the evidence on this subject, a systematic review and meta‐analysis of the currently available literature evaluating the association between the destination hospital's capability (cardiac resuscitation center or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Regionalized systems of post-resuscitation care have been proposed to improve survival outcomes of OHCAs through centralization of highly resource-intensive treatments such as TTM, acute cardiac care including PCI, and multimodal neuro-intensive care. In recent systematic review and meta-analysis, direct transport of OHCA patients to CACs by EMS providers was associated with increased survival outcomes, despite very low certainty of evidence [8,9]. In meta-analysis studies, the definition of CAC varied from study to study, and the capability of PCI was essential, while availability for TTM was treated as important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regionalized systems of post-resuscitation care have been proposed to improve survival outcomes of OHCAs through centralization of highly resource-intensive treatments such as TTM, acute cardiac care including PCI, and multimodal neuro-intensive care. In recent systematic review and meta-analysis, direct transport of OHCA patients to CACs by EMS providers was associated with increased survival outcomes, despite very low certainty of evidence [8,9]. In meta-analysis studies, the definition of CAC varied from study to study, and the capability of PCI was essential, while availability for TTM was treated as important.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines for post-resuscitation care recommend regionalization to designated cardiac arrest centers (CAC) that can provide 24 h immediate PCI and can provide TTM [5,7]. However, in recent systematic review and meta-analysis studies, it was suggested that while transporting patients directly to a CAC did associate with improved clinical outcomes at hospital discharge, it did not improve 1-month survival outcomes [8,9]. Sudden cardiac arrest is one of the most time-sensitive diseases, and the increased transport time interval in bypassing the nearest hospital to reach the destination hospital may be detrimental for some OHCA patients with specific conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that survival to hospital discharge is improved for OOHCA that is witnessed by a bystander/EMS (Emergency Medical Service), in patients who received bystander CPR, in patients with shockable rhythms, and in patients who were able to achieve in-field return of spontaneous circulation (ROSC) [10]. Furthermore, it has been shown that patients who suffer from OOHCA have improved outcomes when transported to medical centers that are specialized and capable of managing cardiac resuscitation with available services such as cardiac catheterization [11]. When considering IHCA, the chain of survival is not as prominent in ensuring improved survival, as patients theoretically are already at the highest level of care required to manage this condition.…”
Section: Cardiac Arrest and Predictors Of Survivalmentioning
confidence: 99%
“…1 Transport to a cardiac resuscitation center has been associated with increased survival and improved short-and long-term outcomes. [81][82][83][84][85] These specialty care centers can offer PCI, cardiac and neurologic critical care and TTM. For unstable patients, active engagement of a critical care transport team is crucial when arranging interfacility transport.…”
Section: Transfer To Specialty Care Centermentioning
confidence: 99%